Informalidad y retos laborales en el municipio de cumaral : bases para la formulación e implementación de una política pública de empleo, emprendimiento y trabajo decente (2021)
This consulting report offers an analysis of the possible barriers that impede the economic growth of the municipality of Cumaral, Meta. Inspired by the growth diagnostics methodology, it analyzes the main usual suspects that impede economic growth in order to determine the challenges and limitations of the local working market and offer recommendations to the municipal administration for the formulation and implementation of a policy public employment, entrepreneurship and decent job.